2020
DOI: 10.1039/c9ta12573f
|View full text |Cite
|
Sign up to set email alerts
|

Fast production of zinc–hexamethylenetetramine complex microflowers as an advanced sulfur reservoir for high-performance lithium–sulfur batteries

Abstract: Hierarchical zinc–hexamethylenetetramine complex microflowers were developed to establish a multifunctional interlayer towards high-capacity and durable lithium–sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…5−8 In an earlier work by Arava and co-workers, the noble metals Pt and Au with electrocatalytic effects on the charge−transfer kinetics in the redox reaction of LiPSs have been investigated where the batteries exhibited reduced overpotential and an improved capacity retention. 9,10 To date, research works have been extended to a wide variety of polar materials with catalytic effects, such as functionalized carbons, 11−13 metal oxides, 14,15 sulfides, 16−19 carbides, 20−22 nitrides, 23,24 and metal−organic frameworks, 25,26 and is considered an effective way for improving the cycling stability of sulfur electrodes. 27−29 As an example, Zhang et al found that the pyrite cobalt disulfide (CoS 2 ) exhibited a high electrocatalytic activity for polysulfide conversion due to the strong adsorption and presence of activation sites on CoS 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5−8 In an earlier work by Arava and co-workers, the noble metals Pt and Au with electrocatalytic effects on the charge−transfer kinetics in the redox reaction of LiPSs have been investigated where the batteries exhibited reduced overpotential and an improved capacity retention. 9,10 To date, research works have been extended to a wide variety of polar materials with catalytic effects, such as functionalized carbons, 11−13 metal oxides, 14,15 sulfides, 16−19 carbides, 20−22 nitrides, 23,24 and metal−organic frameworks, 25,26 and is considered an effective way for improving the cycling stability of sulfur electrodes. 27−29 As an example, Zhang et al found that the pyrite cobalt disulfide (CoS 2 ) exhibited a high electrocatalytic activity for polysulfide conversion due to the strong adsorption and presence of activation sites on CoS 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hence, an accelerated reaction kinetics of the above during discharge/charge would help to reduce the dissolution of polysulfides in the electrolyte, thereby improving the sulfur utilization and reducing their adverse effect on the cycling stability. In an earlier work by Arava and co-workers, the noble metals Pt and Au with electrocatalytic effects on the charge–transfer kinetics in the redox reaction of LiPSs have been investigated where the batteries exhibited reduced overpotential and an improved capacity retention. , To date, research works have been extended to a wide variety of polar materials with catalytic effects, such as functionalized carbons, metal oxides, , sulfides, carbides, nitrides, , and metal–organic frameworks, , and is considered an effective way for improving the cycling stability of sulfur electrodes. As an example, Zhang et al found that the pyrite cobalt disulfide (CoS 2 ) exhibited a high electrocatalytic activity for polysulfide conversion due to the strong adsorption and presence of activation sites on CoS 2 . Although these strategies have been further investigated with density functional theory (DFT) computations to gain atomic-level understanding of LiPS adsorption energy and sites, there remains ambiguity on the binding energy, considering the dynamic nature of LiPSs on the polar interface, especially during the process of the formation of Li 2 S 2 /Li 2 S. Recent studies disclosed that too strong binding energy may induce the decomposition of LiPS species, causing it to detach from the carrier materials. Thus, a comprehensive consideration of the interfacial effect of the carrier material must be taken to achieve an optimized reaction kinetics of LiPSs and consequently enhanced battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.6(a) Cycling stability and coulombic efficiency of Li-S pouch cells with the UHEI@PP and PP separator at 0.2C with a high sulfur loading (4.1 mg cm À2 per side, double sides) and lean electrolyte (E/S ratio ¼ 10 mL mg À1 ) for 100 cycles. (b) Comparison of the IEI and I/S of our UHEI@PP with previous reports from the specific capacity (Z mass ) aspect ( : this work, : CGF (mesoporous cellular graphene framework, Advanced Science, 2016),41 : NCM (NbC-coated membrane, Advanced Functional Materials, 2018),29 : ZnHMT (zinc-hexamethylenetetramine coordination complex, Journal of Materials Chemistry A, 2020),42 : AS PC-Sn 4 P 3 (acorn shell porous carbon/Sn 4 P 3 nanodot, Nano Energy, 2020),39 : HC-PDDA (poly(diallyl dimethyl ammonium chloride) on honey comb-like porous carbon, Energy Storage Materials, 2021),49 : PPZ-HG-CCP (polyphosphazene covalently modified holey graphene/carbonized cellulose paper, Advanced Materials, 2021),50 : PM (0.4 M)-CNT (porous Mxene membrane, Small, 2021), 51 M x N y : (M: metal, N: nonmetal)).…”
mentioning
confidence: 73%
“…[3][4][5] The catalytic materials have been highly needed to alleviate the shuttle effect through the adsorption capacity capturing LiPSs and catalytic activity promoting the LiPSs conversion. [6][7][8][9][10] Polar transition metal compounds attracted much attention as catalytic materials due to the polar surfaces equipped with strong adsorption and feasible reaction with sulfur species. [11][12] Among them, metal oxides and nitrides have excellent adsorption capacity and conductivity respectively.…”
Section: Introductionmentioning
confidence: 99%